Child Homicide Amounting to Murder in Malaysia: Descriptive Analysis of the Statistics and Causes - Razali, Salmi; Jaris, Nor Hidayah; Muuti, Muhamad Zaid; Abdullah, Nuraisyah Chua (Frontiers in Psychology, 2022)
Objective: To describe the child homicide rates and examine the circumstances of homicides of children in Malaysia from January 2010 to June 2021. Methods: This is a retrospective secondary analysis of police records on child homicides in Malaysia. Background demographic characteristics of victims, suspected offenders, motives of homicide and rates of child homicide in Malaysia were analyzed descriptively. Results: A total of 332 child homicide cases involving 349 children aged 18 years old and below by 458 suspected offenders were described. The Malaysian rates of child homicide from 2010-2018 fluctuated between 0.28 to 0.37 per 100000 population of children aged 18 and below. The rates show decreasing trend to 0.19 and 0.17 per 100000 population of children aged 18 in 2019 and 2020, respectively. The majority of the victims were Malay, boys, aged 0-5 years old and 16-18 years old. Offenders were likely to be someone known to the victims, including parents, stepparents, and friends, and have unstable income. The main possible motives of homicide are jealousy and revenge, child abuse and feeling distress. Conclusion: The rates of child homicide in Malaysia are lower compared to other countries and show decreasing trend during this COVID-19 pandemic. These findings perhaps are underestimated and should be cautiously interpreted. Nevertheless, the results should inform immediate intervention to target the at-risk groups.